Socio-Cultural: Socio-Cultural Interaction of Magersari with the Royal Family of Kasepuhan Cirebon - Wulandari, Suci; Imawan, Khaerudin (PT FORMOSA CENDEKIA GLOBAL, 2025)
Socio-cultural interaction is an essential element that must be continuously preserved in the safeguarding of cultural heritage sites, including the environment of the Kasepuhan Palace in Cirebon City. The area surrounding the palace is inhabited by a community known as the Magersari residents, who historically have had a special relationship with the palace. The aim of this study is to identify the forms of sacred ceremonies organized by the Kasepuhan Palace authorities and to examine how the Magersari residents engage in socio-cultural interactions within the royal family’s environment—both through direct participation and established communication. Furthermore, the study analyzes the factors that support the continuity of these activities. This research also seeks to explore the perceptions of the general public and visitors regarding the presence of Magersari residents in the palace area. The study employs a qualitative descriptive method, with data collected through field observations, in-depth interviews, and documentation. The findings reveal that the Magersari residents actively participate in sacred events such as Muludan, Suroan, Saparan, and the ceremonial cleansing of gamelan instruments. They also serve as tour guides and vendors in the palace square area. The study concludes that there is a strong and mutually supportive relationship between the Magersari residents and the Kasepuhan royal family, which is manifested through sustained socio-cultural interactions. This relationship is influenced by religious, cultural, economic, environmental, and communicative factors.